2018
DOI: 10.1007/978-1-4939-7808-3_31
|View full text |Cite
|
Sign up to set email alerts
|

Presenting Peptides at the Surface of Potyviruses In Planta

Abstract: Potyviruses are plant viruses with elongated, flexuous virions amenable to modifications in the only viral structural protein, the coat protein (CP). Out of the several theoretically possible modifications to the CP, the one most exploited for peptide presentation is the genetic fusion of the peptide-to-be-expressed, to the CP N-terminus. Successful high-level expression of the modified CP has been achieved this way. The purified recombinant viral particles incorporate most, if not all, the properties of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…VNPs were purified either from Indian mustard (150 g) or N . benthamiana (100 g) plant material as described 10 . Briefly, plant tissue was finely ground in 0.5 M potassium phosphate pH 7.5, 1:2 (w/v) in an electrical tissue grinder, at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…VNPs were purified either from Indian mustard (150 g) or N . benthamiana (100 g) plant material as described 10 . Briefly, plant tissue was finely ground in 0.5 M potassium phosphate pH 7.5, 1:2 (w/v) in an electrical tissue grinder, at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Elongated flexible viruses with helical symmetry can be modified at the level of their CP by genetic engineering or chemical conjugation 9 , and can be used for delivery, imaging, and theranostics purposes. Virions with introduced peptides in their CPs present the antigen in a repetitive and symmetrical way, and it has been shown that they serve as efficient vaccine platforms 10,11 . Virus like particles (VLPs) devoid of the viral genome are also good nanobiotechnological tools.…”
Section: Introductionmentioning
confidence: 99%
“…VNPs were purified either from Indian mustard (150 g) or N. benthamiana (100 g) plant material as described . Briefly, plant tissue was finely ground in 0.5 M potassium phosphate, pH 7.5, 1:2 (w/v), in an electrical tissue grinder, at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“… 2005 , Chen et al . 2007 , Majer, Navarro and Daròs 2015 ); VIII indicates the CP N terminus, which has been used for heterologous peptide expression (Sánchez and Ponz 2018 ). Sites involved in natural gene gain events are in cyan.…”
Section: Biotech Appeal Of Non-core Modulesmentioning
confidence: 99%